2018
DOI: 10.1007/s40368-017-0323-7
|View full text |Cite
|
Sign up to set email alerts
|

Root lengthening with apical closure in two maxillary immature permanent central incisors after placement of mineral trioxide aggregate (MTA) as an apical plug

Abstract: Unexpectedly, a regeneration of mineral tissues beyond the MTA plug occurred which is an uncommon outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Mineralised tissues produced during apexification can include bone, cementum, dentin or osteodentin (14,19). After trauma, if portions of the formative cells of the periapical area remain vital, then some degree of apexogenic activity may be anticipated which can advance root lengthening (8). These formative tissues include stem cells of the apical papilla (SCAP) and cells from Hertwig’s epithelial root sheath (HERS) (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineralised tissues produced during apexification can include bone, cementum, dentin or osteodentin (14,19). After trauma, if portions of the formative cells of the periapical area remain vital, then some degree of apexogenic activity may be anticipated which can advance root lengthening (8). These formative tissues include stem cells of the apical papilla (SCAP) and cells from Hertwig’s epithelial root sheath (HERS) (20).…”
Section: Discussionmentioning
confidence: 99%
“…Treatments that promote root‐end closure or encourage radicular elongation in traumatised immature teeth include strategies employing calcium hydroxide (CH), mineral trioxide aggregate (MTA), other calcium silicate cements (CSCs) or regenerative endodontic treatments (RETs). Recent investigations have shown that MTA apical plug placement, paired with composite restorations, shows remarkable success in providing predictable treatments that retain traumatised immature devitalised teeth for extended periods (4–8). Moreover, outcome studies of various treatment modalities that encourage root‐end closure have shown MTA apical barriers to be a comparable option to RET’s and CH procedures for immature teeth (9–11).…”
Section: Introductionmentioning
confidence: 99%
“…The exclusion criteria include the following: [1] patients with systemic disorders and bone metabolic diseases such as diabetes, osteoporosis or hypo/hyperparathyroidism and using a medication; deep pockets with generalised chronic periodontitis in teeth (>3 mm); sinus tract swelling; tenderness on palpation and percussions; enlargement of periapical lesion; multiple roots and canals; external/internal resorptions; root fractures; and apical resections, [2] cases treated less than 1 year ago [3] and images with any intraosseous pathology.…”
Section: Methodsmentioning
confidence: 99%
“…The MTA plug shows good clinical success with immediate obturation and rigid barrier formation and addition. Recent publications have reported that the MTA plug allows for greater root development [2, 7]. However, it does not provide an increase in root sizes that are prone to fracture [8].…”
Section: Introductionmentioning
confidence: 99%
“…Apical plug is described as non-surgical compaction of biocompatible material into the apical portion of the root canal that prevents the infiltration of toxins and bacteria into periradicular tissues [11,12]. This barrier enables the placement of an appropriate root canal sealant and filling material while reducing the possibility of their extrusion into periapical tissues, preventing overfilling and promoting periapical healing [7,12,13].…”
Section: Introductionmentioning
confidence: 99%